Diagnostic implications of mycetoma derived from Madurella pseudomycetomatis isolates from Mexico. (15th May 2020) - Nyuykonge, B.; Klaassen, C.H.W.; Zandijk, W.H.A.; de Hoog, G.S.; Ahmed, S.A.; Desnos‐Ollivier, M.; Verbon, A.; Bonifaz, A.; van de Sande, W.W.J.
Abstract: Background: At the dermatology service of the General Hospital of Mexico City, Mexico, two patients, father and son, with black‐grain mycetoma were seen. The grains were isolated, and the cultured fungi were identified as Madurella mycetomatis based on morphology. Using the M. mycetomatis specific PCR, amplicons of a different size than that of the M. mycetomatis type strain were obtained. Objective: To determine the causative agent of the two black‐grain mycetoma cases and develop non‐culture‐based diagnostic tools to identify them to the species level. Methods: The M. mycetomatis specific, the internal transcribed spacer (ITS) region, β‐tubulin (BT) and ribosomal binding protein 2 (RBP2) PCRs were used to confirm the identity of the isolates. Genetic variation was established by amplification fragment length polymorphisms. To determine the antifungal susceptibility profile, the Sensititre™ YeastOne™ assay was used. To develop a species‐specific PCR primers were designed on the sequenced PCR amplicon from the M. mycetomatis specific PCR. Results: By analyzing the ITS, BT and RBP2 regions the isolates were identified as Madurella pseudomycetomatis . The isolates from father and son were similar but not identical to M. pseudomycetomatis from Venezuela and one from an unknown origin. Madurella pseudomycetomatis isolates were inhibited by itraconazole, posaconazole and voriconazole but showed increased MIC values for amphotericin B and fluconazole. They were not inhibited by the echinocandins and five flucytosine. The two patients were treated with itraconazole resulting in cure for the father while the son was lost to follow‐up. The species‐specific PCR developed for M. pseudomyceotmatis was discriminative and specific. Conclusion: Madurella pseudomycetomatis is genetically diverse with same susceptibility profile as M. mycetomatis and causes eumycetoma in Latin America. The M. pseudomycetomatis specific PCR can be used to identify this causative agent to the species level; however, this needs to be validated in an endemic setting.